Surgical Management of Civilian Gunshot-Induced Spinal Cord Injury: Is It Overutilized?. Issue 2 (15th January 2017) - Nwosu, Kenneth; Eftekhary, Nima; McCoy, Eric; Bhalla, Amandeep; Fukunaga, Dudley; Rolfe, Kevin
Abstract : Study Design: Retrospective chart review. Objective: Assess appropriate utilization of surgery for civilian gunshot-induced spinal cord injuries (CGSWSCI) according to literature standards in a large cohort. Summary of Background Data: CGSWSCI are mechanically stable injuries that rarely require surgery. Nonetheless, we continue to see high numbers of these patients undergo surgical treatment. This study compares indications for surgeries performed in a large cohort of CGSWSCI patients to established indications for surgical management of such injuries. The rate of over-utilization of surgical management was calculated. Methods: Four hundred eighty-nine CGSWSCI patients transferred for rehabilitation to our institution between 2000 and 2014 were identified. Retrospective chart review was performed to identify patients who underwent initial surgical treatment, the specific surgeries performed, and indications given. We assessed appropriateness of surgery according to literature standards. Patients treated surgically were followed to assess for complications and the need for additional intervention and compared to nonsurgical patients. Secondarily, visual analog scale pain scores (0–10) and patient perceived improvement were compared between surgical and nonsurgical patients after telephone survey of both groups. Results: Of 489 patients, 91 (18%) underwent initial surgery. Of 91 surgeries, 69 (75%) were not indicated by literature standards. Five of 91 (5.5%) of initially operated patients required a secondary surgery compared with two of 398 (0.5%) of the nonoperative group ( P = 0.003). Over-utilization rate of the entire cohort was 14.1%. No difference was seen for pain scores or patient perceived improvement between operative and nonoperative patients. Conclusion: We report a high overutilization rate (14%) of surgery for CGSWSCI in our cohort. Surgical management was associated with higher infection and secondary surgery rates compared to nonsurgical management. Surgery done without a clear, demonstrable benefit poses unnecessary risk to patients and accumulates unwarranted healthcare costs. Level of Evidence: 3